1997
DOI: 10.1152/jappl.1997.82.5.1416
|View full text |Cite
|
Sign up to set email alerts
|

Combined myofibrillar and mitochondrial creatine kinase deficiency impairs mouse diaphragm isotonic function

Abstract: atine kinase deficiency impairs mouse diaphragm isotonic function. J. Appl. Physiol. 82(5): 1416-1423,1997.-Creatine kinase (CK) is an enzyme central to cellular high-energy phosphate metabolism in muscle. To characterize the physi ological role of CK in respiratory muscle during dynamic contractions, we compared the fore e-velocity relationships, power, and work output characteristics of the diaphragm (Dia) from mice with combined myofibrillar and sarcomeric mitochondrial CK deficiency (CK [-7-]) with CK-suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…These results support the idea that only a minimal level of CK is required for proper contractile function independent of localization. Initial results for heart and diaphragm from the M-CK KO mice indicate these tissues function like control, probably due to sufficient amounts of mitochondrial CK (43)(44)(45). Alternatively, it may be that localization of CK to other structures is important and that BB-CK is properly localized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support the idea that only a minimal level of CK is required for proper contractile function independent of localization. Initial results for heart and diaphragm from the M-CK KO mice indicate these tissues function like control, probably due to sufficient amounts of mitochondrial CK (43)(44)(45). Alternatively, it may be that localization of CK to other structures is important and that BB-CK is properly localized.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MM-CK has been shown to be associated with the sarcoplasmic reticulum, and recent evidence indicates that there are defects in calcium handling in M-CK KO and combined mitochondrial and M-CK KO mice (46). Finally, it is possible that metabolic adaptations substitute for any function of the localized forms of CK (43)(44)(45), although little evidence of adaptation was found in the switch muscle. Rather than serve a specific function, it may be that localization of metabolic enzymes to subcellular structures occurs to avoid macromolecular crowding in general in the cell (47).…”
Section: Discussionmentioning
confidence: 99%
“…Watchko et al (23) created mutant mouse strains missing either or both forms of creatine kinase and compared functional diaphragm muscle performance with controls during isotonic activation. Both singly mutated forms showed no difference from controls in force velocity, power, time of sustained shortening, and work output, whereas in the doubly mutated animal CK [Ϫ͞Ϫ], these were somewhat reduced.…”
Section: The Relative Role Of Pcr and Glycogen During Millisecond Conmentioning
confidence: 99%
“…Several studies have demonstrated that the inhibi tion of the M CK activity immediately reduces the intensity and power of muscle contractions [6][7][8][9] and results in enhanced oxygen uptake by the contracting muscles [10].…”
mentioning
confidence: 99%